A New Global Array of Optical Telescopes: The Falcon Telescope Network. (30th July 2018) - Chun, Francis K.; Tippets, Roger D.; Strong, David M.; Della-Rose, Devin J.; Polsgrove, Daniel E.; Gresham, Kimberlee C.; Reid, Joshua A.; Christy, Casey P.; Korbitz, Mark; Gray, Joel; Gartin, Stanton; Coles, David; et al.
Abstract: We present a new global array of small aperture optical telescopes designed to study artificial satellites and the nearby universe: the Falcon Telescope Network (FTN). Developed by the Center for Space Situational Awareness Research in the Department of Physics at the United States Air Force Academy (USAFA), the FTN is composed of 12 observatories in the United States, Chile, Germany, and Australia, with a potential site in South Africa. The observatory sites were strategically selected with the main objective that once in operation, the telescopes will be capable of working together to perform simultaneous and/or continuous observations of a single object in the sky. This capability allows the observation of artificial satellites from different baselines in a wide range of orbits, continuous data acquisition of variable astronomical sources, and rapid response observations of transient phenomena that require almost immediate follow-up (gamma-ray bursts, novae, or supernovae, etc.). Consisting of commercially available equipment, each observatory is equipped with a 0.5 m primary mirror telescope, a CCD camera, photometric filters, including a special filter to detect exoplanets, and a diffraction grating. The FTN is designed for remote and robotic operation with a host of automation software and services housed on the site computers and at USAFA. FTN partners will have access to a web-based interface where both the observation application as well as the raw data obtained by any of the Falcon nodes will be available. The FTN is a collaborative effort between the USAFA and educational or research institutions on four continents, demonstrating that, through the cooperation of multiple institutions of different levels and capabilities, high-level scientific and educational programs can be carried out, regardless of the geographic location of the various network members.